Synthesis of a Novel Sandwich Copper Complex [(TACN)2Cu](ClO4)2·H2O - Hu, Nai-Liang; Dong, Hua-Ze; Huang, Zi-Xiang; Xie, Fu-Xin (Asian Journal of Chemistry, 2016)
A novel sandwiched copper(II) complex with the ligand 1,4,7-triazacyclononane has been synthesized and characterized by using X-ray diffraction analysis. The results indicate that its crystallographic structure is monoclinic, possessing parameters: P2(1)/c, a = 9.5896(3) Å, b = 13.5820(10) Å, c = 9.5850(3) Å, a = 90.00º, b = 119.3850(10)º, g = 90.00º, n = 1087.79(5) Å3, Z = 2, Dx = 1.627 mg cm–3, R = 0.0560, wR = 0.1548, F(000) = 550.